2012
DOI: 10.1515/njawhe-2012-1108
|View full text |Cite
|
Sign up to set email alerts
|

Women Faculty at Risk: U.S. Professors Report on their Experiences with Student Incivility, Bullying, Aggression, and Sexual Attention

Abstract: In this study of a random sample of 524 professors (47% women, 83% White) from 100 colleges and universities across the United States, 91% reported at least one act of student incivility/bullying, 25% experienced at least one sexual behavior from a student, and 1-2% said a student had used or threatened them with violence in the past year. Women, minorities, younger faculty, and those with less experience and credentials reported more incivility/bullying from students. More women (63.3%) than men (50.2%) repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
68
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 12 publications
7
68
0
2
Order By: Relevance
“…Over the past five years, researchers have documented that ACPH is a routine part of being a professor in the 21 st century (DeSouza, 2011; Lampman, 2012; Lampman et al, 2009). Lampman et al (2009) surveyed all faculty ( n = 399; 61% response rate) at a public university about ACPH across their entire careers ; 96% of women faculty and 99% of men faculty reported at least one act of student incivility-bullying, and 26% of women faculty and 37% of men faculty reported unwanted sexual attention from a student.…”
Section: Prevalence Of Acphmentioning
confidence: 99%
See 4 more Smart Citations
“…Over the past five years, researchers have documented that ACPH is a routine part of being a professor in the 21 st century (DeSouza, 2011; Lampman, 2012; Lampman et al, 2009). Lampman et al (2009) surveyed all faculty ( n = 399; 61% response rate) at a public university about ACPH across their entire careers ; 96% of women faculty and 99% of men faculty reported at least one act of student incivility-bullying, and 26% of women faculty and 37% of men faculty reported unwanted sexual attention from a student.…”
Section: Prevalence Of Acphmentioning
confidence: 99%
“…Incivility was the most common form reported (96%), followed by sexual (31%), and racial-ethnic (11%) harassment. Most recently, Lampman (2012) surveyed a random sample of professors ( n = 524; 66% response rate) from 100 U.S. colleges and universities about ACPH experienced during the past year ; 91% reported at least one type of student incivility/bullying, 25% reported unwanted sexual attention from a student, and 1-2% said a student had been violent toward them or threatened them with violence. Although all of these researchers reported that most professors are likely to experience minor forms of ACPH (e.g., incivility) on a regular basis, the data present a mixed picture when it comes to faculty predictors of ACPH.…”
Section: Prevalence Of Acphmentioning
confidence: 99%
See 3 more Smart Citations